In vitro digestion of luteinizing hormone releasing hormone analog (LHRHa) using simulated gastric conditions in assessing human food safety. (1st February 2016) - Su, Baofeng; Wu, Yonnie; Shang, Mei; Penton, Tom; Lawrence, Sam; Dunham, Rex A.
Highlights: Simulated gastric acid and pepsin were used to digest LHRHa in vitro . Two small fragments from in vitro digestion of LHRHa were quantitatively analyzed using UPLC–MS. LHRHa was completely digested in the simulated human stomach. LHRHa applied as a fish spawning aid would not pose a human food safety risk. Abstract: Luteinizing hormone releasing hormone analog (LHRHa, des Gly10, [D-Ala6] ethylamide) is routinely applied for induced spawning of fish. Simulated gastric acid and pepsin were used to mimic human digestion in vitro to determine the stability of LHRHa upon possible ingestion. In vitro cleavage of LHRHa was quantified using UPLC–MS, ultra-performance liquid chromatography-mass spectrometry. LHRHa was broken down mainly into two fragments from Glp-His-Trp-Ser-Tyr-D-Ala-Leu-Arg-Pro-NHEt (LHRHa) to Trp-Ser-Tyr-D-Ala-Leu-Arg-Pro-NHEt (fragment 1) and Ser-Tyr-D-Ala-Leu-Arg-Pro-NHEt (fragment 2). By 24 h of incubation, LHRHa was completely digested or barely detectable if the starting material was at 250 ng/μl. If the starting concentration was at 5 ng/μl, LHRHa was completely digested by 5 h of incubation, or earlier. In both extreme scenarios, the results indicated that LHRHa would be digested completely in the human stomach and would pose no risk in human food consumption. This study supports the assertion that LHRHa used as a spawning aid would not pose a human food safety risk.